Shorter antibiotic courses in community-acquired pneumonia—ready for prime time - Shaddock, Erica J.; Feldman, Charles (Journal of Thoracic Disease, 2016)
neumonia causes a significant burden of disease in the world, second only to ischaemic heart disease (1). Whilst the major burden of pneumonia is felt in low and middle income countries, it is, importantly, the leading cause of death from infection in the United States (2). Hence the global impact of community-acquired pneumonia (CAP), especially its mortality and morbidity, is often cited as an important reason for improving care in these patients.